2019
DOI: 10.1177/1086296x19833577
|View full text |Cite
|
Sign up to set email alerts
|

Working Toward a Socially Just Future in the ELA Methods Class

Abstract: This review of literature highlights the efforts teacher educators and researchers have made over the past 18 years to work toward social justice in secondary English language arts (ELA) preservice teacher (PT) education. Drawing on Dantley and Green’s framework for social justice leadership, we highlight the work that teacher educators have engaged in to support secondary ELA PTs in developing (a) indignation/anger for justice through exploring beliefs about students and themselves, (b) a prophetic and histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Statistical power analysis executed in G*Power 3.1.9.7 determined the minimum sample size of 407 required for the study. The power analysis estimations factored significance, effect size, and power as calculation criteria [67]. The sample size of 407 is higher than the sample sizes used in comparative studies [27,[68][69][70].…”
Section: Methodsmentioning
confidence: 99%
“…Statistical power analysis executed in G*Power 3.1.9.7 determined the minimum sample size of 407 required for the study. The power analysis estimations factored significance, effect size, and power as calculation criteria [67]. The sample size of 407 is higher than the sample sizes used in comparative studies [27,[68][69][70].…”
Section: Methodsmentioning
confidence: 99%
“…Texts should not be limited to traditional notions of print-based artifacts, as myriad digitized or performative means of eliciting literacy engagement can help strengthen cultural and linguistic relevance for secondary learners (Petrone et al , 2015). Fowler-Amato et al (2019) argue, “opening up what counts as text, genre, language, and literacy practice has the potential to support PTs in developing understandings about not only the young people they teach but also the communities that are home to these young people” (p. 171). Moreover, contemporary views of book-length texts illuminate literacy practices within disciplines, which operate via highly specialized means of language and interaction (Gee, 1989).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, experiences that positioned preservice teachers as writers, encouraged them to “thoughtfully (and…collaboratively)” examine the writing of students, and positioned students as “capable readers and writers” (p. 207) were all important. Similarly, Fowler‐Amato, LeeKeenan, Warrington, Nash, and Brady (2019) found that there has been a concerted effort to broaden English language arts preservice teachers’ disciplinary understandings through critique of historical knowledge, tools, and practices historically valued in English language arts classrooms. Additionally, Fowler‐Amato et al documented how teacher education programs are thinking carefully about socially just teaching in clinical field experiences and how to negotiate the tensions between preservice teachers’ program and field placement experiences.…”
Section: Research On Literacy Teacher Preparationmentioning
confidence: 99%
“…For example, how reading, writing, and/or literacy were defined in the research was not always clearly articulated; as a result, it seemed that traditional notions of reading versus writing are still prominent (see Bomer et al, 2019; Hikida et al, 2019). Similarly, much of the research in these syntheses looked at preservice teacher preparation in a single semester and in one context, rather than across time and space (see Fowler‐Amato, LeeKeenan, et al, 2019; Hoffman et al, 2019). Finally, as a way of radically reimagining literacy instruction in teacher education (Sailors, 2019), the work of Flores et al (2019) and Mosley Wetzel et al (2019) suggested that research in literacy teacher education should be used to dismantle hegemony.…”
Section: Research On Literacy Teacher Preparationmentioning
confidence: 99%